The Perils of Protest State Repression and Student Activism in China and Taiwan - Wright, Teresa (University of Hawaii Press, 2001)
China's student movement of 1989 ushered in an era of harsh political repression, crushing the hopes of those who desired a more democratic future. Communist Party elites sealed the fate of the movement, but did ill-considered choices by student leaders contribute to its tragic outcome? To answer this question, Teresa Wright centers on a critical source of information that has been largely overlooked by the dozens of works that have appeared in the past decade on the "Democracy Movement": the students themselves. Drawing on interviews and little-known first-hand accounts, Wright offers the most complete and representative compilation of thoughts and opinions of the leaders of this student action. She compares this closely studied movement with one that has received less attention, Taiwan's Month of March Movement of 1990, introducing for the first time in English a narrative of Taiwan's largest student demonstration to date. Despite their different outcomes (the Taiwan action ended peacefully and resulted in the government addressing student demands), both movements similarly maintained a strict separation between student and non-student participants and were unstable and conflict-ridden. This comparison allows for a thorough assessment of the origins and impact of student behavior in 1989 and provides intriguing new insights into the growing literature on political protest in non-democratic regimes
Description based on online resource; title from PDF title page (publisher's Web site, viewed 19. Jan 2018)
Keywords: Geschichte 1989-1990; Students -- Political activity; Students -- China; Students -- Taiwan; Student; Politisches Handeln; China; Taiwan